2002
DOI: 10.1002/jmri.10177
|View full text |Cite
|
Sign up to set email alerts
|

1H and 31P spectroscopy and bioenergetics in the lateralization of seizures in temporal lobe epilepsy

Abstract: Over the past decade, 1 H and 31 P spectroscopy measurements have demonstrated that significant metabolic alterations occur in temporal lobe epilepsy. However, to most accurately interpret these changes, metabolic heterogeneity and differences between gray and white matter must be accounted for. These alterations, decreased NAA and the ratio of phosphocreatine/inorganic phosphate, can be reversed with successful treatment of seizures. The reversibility of these two measures is consistent with the localization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
35
0
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 49 publications
5
35
0
5
Order By: Relevance
“…Although we did not perform corrections for tissue type using segmentation methods (12), the NAA/Cre ratios differed significantly among brain regions and were comparable to those represented graphically by Tkac et al (7).…”
Section: Discussionsupporting
confidence: 77%
“…Although we did not perform corrections for tissue type using segmentation methods (12), the NAA/Cre ratios differed significantly among brain regions and were comparable to those represented graphically by Tkac et al (7).…”
Section: Discussionsupporting
confidence: 77%
“…Several studies of schizophrenia have reported the following decreases in NAA content, most of which would have been sizable enough for detection in our study: 31% (p = 0.005) in prefrontal cortex [9], 12% (p = 0.005) in frontal lobe [24], 17% (p < 0.05) [25] and 56% (p < 0.001) [26] in dorsolateral prefrontal cortex (DPFC). Of these, the one that showed the greatest decrease in NAA [26] was the only one that corrected for varying gray matter content, which has been shown to improve ability to detect changes [27]. Since cortical atrophy has been measured in schizophrenia [12], correction for neuron and water content could increase our ability to measure changes.…”
Section: Discussionmentioning
confidence: 99%
“…31 P MRS allows noninvasive assessment of various fundamental biochemical, physiological, and energy intensive metabolic events occurring inside the brain (31,32). The steady-state phosphate signals as well as other physiological parameters detected by in vivo 31 P MRS have been used extensively in clinical studies and linked to numerous diseases such as AD (33), epilepsy (34,35), migraine, brain ischemia, and seizure (36). To enhance the signal-to-noise ratio (SNR) of the MR spectrum, the pulse sequence and the parameters are adjusted to minimize signal intensity loss due to T 2 (transverse) and T 1 (longitudinal) relaxation of the nuclei (e.g., 1 H, 31 P, and 13 C).…”
mentioning
confidence: 99%